Research Progress on the Role of Microorganisms in the Remediation of Saline-alkali Land - Ruibo SUN; Fengling ZHANG; Jingwen ZONG; Cong LUO; Kaixuan LI; Ying WANG; Lin CHEN (Guangdong nongye kexue)
Saline-alkali land, serving as a crucial reserve land resource, is widely distributed in China. Enhancing soil quality to unlock the agricultural potential of these lands is of great importance to ensure national food security and promote sustainable socioeconomic development. Notably, saline-alkali soils harbor diverse microbial resources with multifaceted functions. As the most active components within soil ecosystems, microorganisms play pivotal roles in improving soil structure, enhancing soil fertility, and facilitating plant growth. The strategic exploitation of these microbial resources represents a promising approach for saline-alkali soil remediation. Nevertheless, substantial challenges persist in developing microorganism-based amelioration technologies, as there are still lack of comprehensive understanding of microbial community assembly mechanisms, pathways for regulating ecological functions, and plant-microbe mutualistic interactions in saline-alkali environments, and the inherent environmental sensitivity of microbial communities further compounds these limitations. This paper summarizes the main functional microbial resources in saline-alkali land, outlines the primary pathways through microorganisms to enhance soil quality, promote plant growth and stress resistance, and boost crop productivity. It also systematically reviews the current main methods and research progress in utilizing microorganisms for saline-alkali soil remediation, and discusses the challenges faced in this progress as well as future research content and directions, with the aim of promoting the development of microbial ecological research in saline-alkali land and providing microbiological solutions for saline-alkali soil remediation.